2003
DOI: 10.1242/dev.00277
|View full text |Cite
|
Sign up to set email alerts
|

Identification of spatial and temporal cues that regulate postembryonic expression of axon maintenance factors in theC. elegansventral nerve cord

Abstract: Patterns of gene expression are under precise spatial and temporal control. A particularly striking example is represented by several members of thezig gene family, which code for secreted immunoglobulin domain proteins required for maintaining ventral nerve cord organization inCaenorhabditis elegans. These genes are coordinately expressed in a single interneuron in the ventral nerve cord, known as PVT. Their expression is initiated at a precise postembryonic stage, long after PVT has been generated in mid-emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…(B) Quantification of rescue data. Note that we have previously shown that overexpression of zig-4, using again the myo-3 promoter, causes PVQ axon outgrowth defects (Aurelio et al 2003). In the experiments shown here myo-3Tzig-4 was injected at lower concentration, which did not result in axon outgrowth defects.…”
Section: Resultssupporting
confidence: 46%
“…(B) Quantification of rescue data. Note that we have previously shown that overexpression of zig-4, using again the myo-3 promoter, causes PVQ axon outgrowth defects (Aurelio et al 2003). In the experiments shown here myo-3Tzig-4 was injected at lower concentration, which did not result in axon outgrowth defects.…”
Section: Resultssupporting
confidence: 46%
“…It has been reported that in lim-6 mutants Pglr-1GFP expression is normal and RMEL/R neurons are normal , indicating that the effect on Pglr-1GFP in ahr-1(ju145) animals is independent of lim-6. In addition, we found that the expression of a transgene Punc-47sGFP that contains a shortened unc-47 promoter, and which is expressed specifically in RMEL/R but not in RMED/V (Aurelio et al, 2003), was abolished in RMEL/R neurons of ahr-1(ju145) animals (Fig. 3G,H).…”
Section: Rmel and Rmer Neurons Adopt An Rmed/v-like Fate In Ahr-1 Mutmentioning
confidence: 87%
“…Genetic nomenclature follows the standard C. elegans system (Horvitz et al, 1979). The GFP reporter strains used are listed below: juIs76 (Punc-25GFP) (Huang et al, 2002), juIs1 (Punc-25SNB-1-GFP) (Zhen and Jin, 1999), oxIs12 (Punc-47flGFP) (McIntire et al, 1997), otIs37 (Punc-47sGFP) (Aurelio et al, 2003), nuIs25 (Pglr-1GFP) (Hart et al, 1995), otEx406 (Plim-6rGFP) , juEx517 (Pavr-15GFP) (Dent et al, 1997) (this study), vbEx1 (Pclh-6GFP) (Bianchi et al, 2001), iaIs2 (AHR-1::GFP) (Qin, H and J.A.P.-C., unpublished). ZG69 aha-1(ia1); iaEx28 was used as the starting strain to examine the role of aha-1 in RME neurons.…”
Section: Methodsmentioning
confidence: 99%
“…Our observations support the idea that some level of Slit/Robo repulsion is required continuously to keep ipsilateral axons on their own side of the midline. A more dramatic example of pathway maintenance has been described in C. elegans, where mutations in the Zig genes lead to a 'flipping' of axon pathways over the midline (Aurelio et al, 2003;Aurelio et al, 2002). Additionally, in Drosophila, it has been shown that ␤-Spectrin is essential for synapse stabilization (Pielage et al, 2005).…”
Section: The Role Of ␤-Spectrin In Midline Repulsion During Growth Comentioning
confidence: 99%